Optimalisasi Strategi Pelayanan dan Pemasaran pada Baitul Maal wa Tamwil (BMT) Usaha Gabungan Terpadu (UGT) Sidogiri - Gunawan, Risma (Maliki Interdisciplinary Journal, 2025)
This study aims to examine the optimization of service and marketing strategies at Baitul Maal wa Tamwil (BMT) UGT Sidogiri in facing the challenges of digitalization and competition. BMT integrates social and commercial functions to empower the people’s economy. The method used is qualitative descriptive with a literature review approach. The results of the study indicate that fast, transparent, and needs-based services increase satisfaction and loyalty. Marketing through word of mouth and the use of digital media can expand customer reach. The challenges faced include limited technology and low financial literacy in the community. BMT is advised to increase human resource capacity, utilize technology optimally, and strengthen financial literacy education. With the right strategy, BMT UGT Sidogiri can maintain its sustainability and continue to play a role in empowering the community’s economy.